SWAT 1: what effects do site visits by the principal investigator have on recruitment in a multicentre randomized trial?. Issue 3 (27th August 2013) - Smith, Valerie; Clarke, Mike; Devane, Declan; Begley, Cecily; Shorter, Gillian; Maguire, Lisa
Abstract The SWAT (Study Within A Trial) programme has been established to develop a series of studies that would embed research within research, so as to resolve uncertainties about the effects of different ways of designing, conducting, analyzing and interpreting evaluations of health and social care. It was described in an Education piece in the Journal of Evidence‐Based Medicine in 2012. We have now prepared the first example of the design summary for a SWAT, using the template that will be used for other SWAT. This is presented in this article.